ARAHAN KEBIJAKAN PENGELOLAAN HUTAN MANGROVE: KASUS PESISIR KECAMATAN TELUK PAKEDAI, KABUPATEN KUBURAYA, PROVINSI KALIMANTAN BARAT - Ritohardoyo, Su; Ardi, Galuh Bayu (Jurnal Geografi, 2014)
General purposes of this research was to assess perceptions and participation inutilization, prevention of mangrove forests damage, to look for an alternativedirection for mangrove forest management to the societies surrounding. Datacollection using surveys, through interviews with a sample of respondents were90 families (KK) or 25 percent of the total population of 358 families. The resultsshowed that the population majority (48.8%) had moderate category knowledgeabout the benefits, the damage effect after use, and the need for prevention ofmangrove forests damage. Most of the population (53.6%) had a low perceptionof the category. This is influenced by the knowledge level of mangrove forests (c= 12.71; significance 0.013). Local government policy to mangrove forestsmanagement, responded negatively by the local community. This was caused bythe absence of mangrove forest management efforts clearly and firmly. Localgovernment should immediately develop a plan of integrated mangrove forestsmanagement, and immediately disseminated to the public around the mangroveforests.